Online Behavioral Advertising Avoidance in Online Retailing in Sri Lanka (Global Journal of Management and Business Research, 2019)
As the rapid growth of technology, there're new advertising trends which can deliver the communication messages to the people more accurately. Therefore, every business connecting with the advertising to aware people and to promote their business. Online Behavioral Advertising (OBA) is a trend which developed with the innovation of technology. It's an advertising technique which decides what to show to the audience after tracking their surfing behavior and purchase history. Though these advertisements are beneficial for the business firm to target their audience accurately, the online users tend to avoid these advertisements due to some reasons. However, there are no adequate studies done on finding the factors behind this ad avoidance behavior. Thus this study shed light on this under-researched area focusing on the development of a conceptual framework based on the identified major reasons behind this ad avoidance.
Keywords: online behavioral advertising; privacy concern; goal impediment; ad skepticism negative experience; perceived personalization